Assessing the impact of national level interventions on workplace respiratory disease in the UK: part 2—regulatory activity by the Health and Safety Executive. Issue 7 (20th April 2013) - Stocks, S J; McNamee, R; Turner, S; Carder, M; Agius, R M
Abstract : Objective: To investigate whether interventions implemented by the UK Health and Safety Executive addressing exposure to isocyanate-based spray paints in motor vehicle repair (MVR), flour dust in craft bakeries, rosin-based solder flux fume (RBSFF) in the electronics industry, metalworking fluids and wood dust coincided with a decline in incidence of work-related short latency respiratory disease (SLRD) or asthma in the target groups. Method: Changes in the incidence of SLRD reported to a UK-based surveillance scheme were compared using a longitudinal, negative binomial regression model with β distributed random effects. An interrupted time series design was used and comparisons according to inclusion or exclusion in the target group were made by including a statistical interactions expressed as a ratio of incidence rate ratios (RIRRs) in the model. Results: The incidence of SLRD attributed to flour dust significantly increased relative to all other agents (RIRR: 1.10; 95% CI 1.06 to 1.16) whereas SLRD attributed to RBSFF significantly declined relative to all other agents (0.94; 0.90 to 0.99). No significant changes in the incidence of SLRD attributed to wood dust (1.03; 0.91 to 1.16) or spray paints (1.03; 0.95 to 1.11) relative to all other agents were observed. A higher proportion of reports originated from the industries targeted by the intervention for RBSFF (65/107; 61%) than spray painting (27/93; 27%) or wood dust (16/42; 38%). Conclusions: These data support a beneficial effect of interventions to reduce exposure to RBSFF but an increase in SLRD attributed to flour dust may indicate increased exposure or increased awareness of the problem.